Frantz Fanon and the New Mexican School: Reflections from Anthropology and Intercultural Pedagogy (Praxis Educativa, 2025)
One hundred years after the birth of Frantz Fanon, his legacy continues to resonate within decolonial studies, particularly through his critique of colonialism and its capacity to permeate the social and cultural systems of oppressed peoples. His works reveal the mechanisms of colonization while simultaneously outlining alternative pathways to dismantle colonial structures and establish free nations. Building on these premises, this essay examines how processes of domination and the ideological reproduction of colonialism have been embedded in Mexico through its educational systems. At the same time, it considers the potential for incorporating Fanon’s principles into the framework of the so-called New Mexican School (Nueva Escuela Mexicana). The discussion presents a series of reflections grounded in anthropological and educational perspectives, exploring Mexico’s historical experience with colonialism and envisioning decolonial possibilities for the construction of new civilizational projects in the 21st century.
Keywords: vocational guidance, inclusive education, higher education.